24TiPKEYNOTE-756: A randomized, double-blind, phase III study of pembrolizumab or placebo with neoadjuvant chemotherapy and adjuvant endocrine therapy for high-risk, early-stage, ER+/HER2−breast cancer. (24th November 2019) - Cardoso, F; Bardia, A; André, F; Cescon, D W; McArthur, H; Telli, M; Loi, S; Cortes, J; Schmid, P; Harbeck, N; Denkert, C; Jackisch, C; et al.
Abstract: Background: A high-risk subpopulation of ER+/HER2− breast cancer (BC) is characterized by high-grade tumors, decreased sensitivity to endocrine therapy (ET), higher responsiveness to chemotherapy (CT), and worse prognosis. Prior studies suggest that increased pathological complete response (pCR) rates after neoadjuvant CT may have a substantial impact for patients with high-risk, early-stage, HR+/HER2− BC. KEYNOTE-756 (NCT03725059) is a global, randomized, double-blind, phase 3 study of pembrolizumab (vs placebo) + CT as neoadjuvant treatment followed by pembrolizumab (vs placebo) + ET as adjuvant treatment for patients with high-risk, early-stage, ER+/HER2− BC. Trial design: Patients with T1c-2 cN1-2 (tumor size ≥2 cm) or T3-4 cN0-2 grade 3, invasive, ductal ER+/HER2− BC will be stratified by lymph node involvement (positive vs negative), tumor PD-L1 status (positive [CPS ≥1] vs negative [CPS <1]), ER positivity (ER + ≥10% vs ER + <10%), and anthracycline dosing schedule (every 3 weeks [Q3W] vs Q2W), then randomized 1:1 to neoadjuvant treatment with pembrolizumab 200 mg Q3W or placebo combined with paclitaxel (80 mg/m 2 Q1W) for 4 cycles followed by doxorubicin (60 mg/m 2 ) or epirubicin (100 mg/m 2 ), each with cyclophosphamide (600 mg/m 2 ) Q2/3W for 4 cycles. After definitive surgery (± radiation therapy, as indicated), patients will receive adjuvant treatment of pembrolizumab (200 mg Q3W) or placebo for 9 more administrations combined with ET, which can be given for up to 10 years. No crossover between treatment cohorts when moving from neoadjuvant to adjuvant treatment is allowed. Dual primary endpoints are pCR rate (ypT0/Tis ypN0) and event-free survival (EFS). Secondary endpoints include ypT0/Tis and ypT0 ypN0 pCR rates in all patients and all 3 pCR definitions in those with PD-L1+ tumors, EFS in patients with PD-L1+ tumors, overall survival, safety, and health-related quality of life. Enrollment is currently ongoing in 22 countries around the world, including Korea, Taiwan, China, and Japan. Clinical trial identification: NCT03725059. Legal entity responsible for the study: Merck & Co., Inc. Funding: Funding for this study was provided by Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Disclosure: F. Cardoso: Advisory / Consultancy: Amgen; Advisory / Consultancy: Astellas/Medivation; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Celgene; Advisory / Consultancy: Daiichi-Sankyo; Advisory / Consultancy: Eisai; Advisory / Consultancy: GE Oncology; Advisory / Consultancy: Genentech; Advisory / Consultancy: GlaxoSmithKline; Advisory / Consultancy: Macrogenics; Advisory / Consultancy: Medscape; Advisory / Consultancy: Merck-Sharp; Advisory / Consultancy: Merus BV; Advisory / Consultancy: Mylan; Advisory / Consultancy: Mundipharma GmbH; Advisory / Consultancy: Novartis; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Pierre-Fabre; Advisory / Consultancy: prIME Oncology; Advisory / Consultancy: Roche. A. Bardia: Advisory / Consultancy, Research grant / Funding (self): bioTheranostics; Advisory / Consultancy: Genentech; Advisory / Consultancy: Genentech/Roche; Advisory / Consultancy: Immunomedics; Advisory / Consultancy: Innocrin Pharmaceuticals; Advisory / Consultancy: Merck; Advisory / Consultancy: Novartis; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Radius Health; Advisory / Consultancy: Radius Pharma; Advisory / Consultancy: Sanofi; Advisory / Consultancy: Spectrum Pharmaceuticals. F. André: Research grant / Funding (institution): Novartis; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Lilly; Research grant / Funding (institution): Roche. D.W. Cescon: Honoraria (self), Advisory / Consultancy: Novartis; Honoraria (self), Advisory / Consultancy: Pfizer; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Genomic Health; Advisory / Consultancy, Research grant / Funding (institution): GlaxoSmithKline; Advisory / Consultancy, Research grant / Funding (institution): Merck; Research grant / Funding (institution): Roche/Genentech. H. McArthur: Advisory / Consultancy: Celgene; Advisory / Consultancy, Research grant / Funding (self): Merck; Advisory / Consultancy: OBI Pharma; Advisory / Consultancy: Roche; Advisory / Consultancy: Spectrum Pharmaceuticals; Advisory / Consultancy: Syndax Pharmaceuticals; Advisory / Consultancy: Peregrine; Advisory / Consultancy: Calithera; Research grant / Funding (self): Bristol-Myers Squibb; Research grant / Funding (self): Eli Lilly; Research grant / Funding (self): MedImmunne; Research grant / Funding (self): LLC/AstraZeneca. M. Telli: Advisory / Consultancy, Research grant / Funding (institution): Merck; Advisory / Consultancy, Research grant / Funding (institution): Genentech; Advisory / Consultancy: Aduro; Advisory / Consultancy, Research grant / Funding (institution): Pfizer; Advisory / Consultancy: Immunomedics; Advisory / Consultancy: Celldex; Advisory / Consultancy, Research grant / Funding (institution): Tesaro; Research grant / Funding (institution): OncoSec; Research grant / Funding (institution): Biothera; Research grant / Funding (institution): Vertex; Research grant / Funding (institution): Calithera; Research grant / Funding (institution): Merck Serono; Research grant / Funding (institution): PharmaMar. S. Loi: Advisory / Consultancy: AstraZeneca/MedImmune; Advisory / Consultancy, Research grant / Funding (institution): Bristol-Myers Squibb; Advisory / Consultancy, Research grant / Funding (institution): Merck; Advisory / Consultancy: Pfizer; Advisory / Consultancy, Research grant / Funding (institution): Roche/Genentech; Advisory / Consultancy: Seattle Genetics; Research grant / Funding (institution): Lilly; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Puma Biotechnology. J. Cortes: Shareholder / Stockholder / Stock options: MedSIR; Honoraria (self), Travel / Accommodation / Expenses: Novartis; Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Eisai; Honoraria (self), Advisory / Consultancy: Celgene; Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Pfizer; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Roche; Honoraria (self): Samsung; Advisory / Consultancy: Cellestia Biotech; Advisory / Consultancy, Research grant / Funding (institution): AstaZeneca; Advisory / Consultancy: Biothera; Advisory / Consultancy: Merus; Advisory / Consultancy: Seattle Genetics; Advisory / Consultancy: Daiichi-Sankyo; Advisory / Consultancy: ERYTECH Pharma; Advisory / Consultancy: Polyphor; Research grant / Funding (institution): ARIAD; Research grant / Funding (institution): Baxalta GmbH; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): Guardant Health; Research grant / Funding (institution): Merck. P. Schmid: Full / Part-time employment: Roche; Honoraria (self), Research grant / Funding (institution): AstraZeneca; Honoraria (self): Bayer; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Celgene; Honoraria (self): Eisai; Honoraria (self), Research grant / Funding (institution): Genentech/Roche; Honoraria (self), Research grant / Funding (institution): Merck; Honoraria (self), Research grant / Funding (institution): Novartis; Honoraria (self): Pfizer; Honoraria (self): Puma Biotechnology; Research grant / Funding (institution): Astellas Pharma; Research grant / Funding (institution): Medivation; Research grant / Funding (institution): Oncogenex. N. Harbeck: Honoraria (self), Advisory / Consultancy: Lilly; Honoraria (self), Advisory / Consultancy: Novartis; Honoraria (self), Advisory / Consultancy: Pfizer. C. Denkert: Honoraria (self), Advisory / Consultancy: Amgen; Honoraria (self): Novartis; Honoraria (self): Pfizer; Honoraria (self): Teva; Honoraria (self): Roche; Shareholder / Stockholder / Stock options: Sividon Diagnostics; Advisory / Consultancy: Daiichi-Sankyo; Advisory / Consultancy: MSD Oncology; Licensing / Royalties, patent application—therapy response: EP20150702464; Licensing / Royalties, patent application— cancer immunotherapy: EP18209672; Licensing / Royalties, digital pathology software: VMScope. C. Jackisch: Honoraria (self), Advisory / Consultancy: Merck. L. Jia: Travel / Accommodation / Expenses, Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck. K. Hirshfield: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck. V. Karantza: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck.